Factors associated with traction alopecia in women living in Yaoundé (Cameroon) - Letitia Fiona Mbussuh Nzeng; Georges Nguefack-Tsague; Dahlia Noëlle Tounouga; Mohamed Maciré Soumah; Franck Albert Armand Mbang; Odette Berline Sigha; Grace Anita Nkoro; Rose Kotto; Emmanuel Armand Kouotou (BMC, 2023)
Abstract Background Traction alopecia (TA) is very common in Africa but few studies on African population are available. We sought to determine factors associated with TA and measure the association between these factors and TA. Methods We carried out an analytical cross-sectional study in 29 hairdressing saloons in the city of Yaoundé. A questionnaire was administered and scalp exams were performed in order to look for TA and determine Marginal TA severity score if present. Participants were separated in two groups: TA group and a group without TA. Results We finally included 223 women (77 having TA and 146 without TA). The median age was 26 years for women with TA and 24 years for women without TA. The factors associated with traction alopecia we found included: age ≥ 35 years (adjusted OR = 4; p = 0.016). Hairdressing undertaken by hairdressers only (adjusted OR = 0.2; p = 0.008), the avoidance of the regular use of nets, caps and head ties (OR = 0.2; p = 0.006) and relaxing hairs once a year or less (adjusted OR = 0.2; p = 0.005) could be protective factors. As well, we found a positive correlation between age and TA severity (r = 0.235; p < 0.001). Conclusion Age and some haircare practices are associated to TA occurrence in our context. Women therefore need to be educated on these various factors that could be able to cause, worsen or prevent TA.